Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.